Co-occurring Trajectories of Direct Aggression and Prosocial Behaviors in Childhood: Longitudinal Associations With Peer Acceptance - Ettekal, Idean; Mohammadi, Minoo (Frontiers in Psychology, 2020)
This study examined the longitudinal associations among children’s direct (physical and verbal) aggression, prosocial behaviors, and peer group acceptance in middle childhood (Grades 1 to 4). Children’s co-occurring aggressive and prosocial behaviors were assessed in order to identify distinct trajectory subgroups. Subsequently, variations in the development (i.e., continuity and changes) in peer acceptance were examined for each of the identified subgroups. The sample consisted of 784 children who were ethnically and socioeconomically diverse (47% girls, 37.4% Latino or Hispanic, 34.1% European American, and 23.2% African American; about 65% low SES) who were followed longitudinally from Grades 1 to 4 (Mage = 6.57 years old in Grade 1). Results revealed several distinct trajectory subgroups, including children who were primarily aggressive or prosocial, as well as children who exhibited co-occurring aggression and prosocial behaviors. Comparing these subgroups, the use of co-occurring prosocial behaviors appeared to have some protective effect on aggressive children’s peer acceptance. However, aggression was nonetheless associated with lower peer acceptance. The findings provide insights pertaining to the heterogeneity among aggressive children, the protective effects of prosocial behaviors on peer acceptance, and the differential effects of moderate versus high aggression.